The situation of mental health of vietnam disabled athletes in weightlifting and javelin before Paralympic Games 2021 - Bao, V. V.; Tuan, T. M. (European Journal of Physical Education and Sport Science, 2023)
The purpose of this study was to find out the situation of Vietnam disabled athletes' mental health before Paralympic Games 2021. Seven athletes from the Vietnam disabled team (including 4 male and 3 female athletes in weightlifting and javelin contents) were chosen to identify their mental health before Paralympic Games. The International Olympic Committee's (IOC) Sports Metal Health Assessment Tool 1 (SMHAT-1) was used to determine the risk or experience of symptoms and mental health disorders of national team athletes with disabilities, facilitating timely referral for athletes in need of adequate support and treatment. The study identified the mental health of disabled Vietnam athletes in weightlifting and javelin. Thus, it led the management and coaches to have a specific plan for the appropriate pre-competition preparation for athletes, thereby getting good results in the upcoming Paralympic Games 2021.